ANALISIS PEMBELAJARAN BERBASIS TPACK PADA PESERTA DIDIK DI KELAS V SDN 2 KANDANGSAPI - Hermawan, Ryco; Syahruroji, A; Nurhasanah, Ana; Yandari, Indhira Asih Vivi (Jurnal Pendidikan Dasar, 2023)
The use of technology in the world of education is certainly very useful and relevant to current conditions. The existence of technology can provide any information needed for learning. The current use of technology in the world of learning is better known as TPACK. This research aims to: 1) Describe the analysis of the TPACK-based learning process. 2) Explain the challenges and efforts of TPACK-based learning. 3) Describe the results of TPACK learning at SDN 2 Kandangsapi. This research uses a qualitative approach with descriptive methods. Where the data collection is in the form of a collection of words and images. So in this research the researcher examined data from interview sources, observation and documentation. The results of this research show that: 1) TPACK can be used as a technology-based learning approach in an effort to adapt technology to current developments. 2) This TPACK approach must be supported by all aspects of supporting learning such as laptops, cellphones, projectors, learning videos and the internet. 3) The impact of TPACK learning can be seen in students' skills in understanding learning material as well as students' skills in using technology.